Doing history - Donnelly, Mark, 1967-; Norton, Claire (London ; New York : Routledge, 2011)
"History as an academic discipline has dramatically changed over the last few decades and has become much more exciting and varied as a res ult of ideas from other disciplines, the influence of postmodernism and historians' incorporation of their own theoretical reflections into th eir work. The way history is studied at university level can vary great ly from history at school or as represented in the media and Doing Hist ory bridges that gap. Aimed at students of history in their final year of secondary education or beginning degrees, this is the ideal introduc tion to studying history as an academic subject at university. "Doing H istory" presents the ideas and debates that shape how we "do" history t oday, covering arguments about nature of historical knowledge and the f unction of historical writing, whether we can really ever know what hap pened in the past, what sources historians depend on, and whether the h istorians' version of history has more value than popular histories. Th is practical and accessible introduction to the discipline introduces s tudents to these key discussions, familiarises them with the important terms and issues, equips them with the necessary vocabulary and encoura ges them to think about, and engage with, these questions. Clearly stru ctured and accessibly written, it is an essential volume for all studen ts embarking on the study of history"--
"Aimed at students beginning degrees, this is the ideal introduction to studying history as an academic subject at university. Doing Histor y presents the ideas and debates that shape how we 'do' history today, covering arguments about nature of historical knowledge and the functio n of historical writing, whether we can really ever know what happened in the past, what sources historians depend on, and whether the histori ans' version of history has more value than popular histories"--
Includes bibliographical references (p. 195-230) and index.
Keywords: History -- Study and teaching (Higher); History -- Methodology